Integrating Apriori Mining and Speech Recognition for Intelligent and Secure Online Classroom Interaction - Zhao, Wei (Informatica, 2025)
Real-time structuring of speech and anomaly detection remain critical challenges in online classroom interactions, especially under noisy and multi-speaker conditions. This study proposes an integrated framework that combines Automatic Speech Recognition (ASR) with Apriori-based pattern mining to enhance the intelligence and security of online classrooms. The system first applies multi-speaker ASR with acoustic feature separation to achieve robust transcription, speaker labeling, and noise suppression. The transcribed text is pre-processed through Chinese word segmentation and stop-word filtering to construct a transactional dataset. Frequent Pattern Growth (FP-Growth) is then employed to generate frequent itemsets and extract high-confidence association rules, forming a reference speech-pattern library. Local anomaly factors are introduced to quantify deviations in support and confidence between new corpora and the rule library, thereby enabling early detection of sensitive or off-topic speech. Experimental validation on 120 classroom sessions demonstrates an 80.2% recognition accuracy in highly noisy environments, with rule coverage and confidence reaching 87% and 89%, respectively. The proposed framework significantly improves anomaly warning efficiency, reducing sensitive-speech combinations by 87.0%. These results highlight the feasibility and effectiveness of integrating ASR and Apriori mining for intelligent speech structuring, pattern extraction, and anomaly detection in secure online classroom environments.